Life in the industrial revolution: The past in question - Paula Bartley (Hodder and Stoughton, 1993)
The book examines how the industrial revolution was largely based on the mechanisation of the cotton industry and encourages pupils to consider the effects of the cotton trade on the lives of ordinary poeple by looking at the social changes brought about by mechanisation and the factory system, reactions to the new system and resulting reform